2008
DOI: 10.1142/s0217979208048772
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Misfit Measurement in Inconel 625 by X-Ray Diffraction Technique

Abstract: Determination of lattice misfit and microstructural parameters of the coherent precipitates in Ni based alloy Inconel-625 is a challenging problem as their peaks are completely overlapping among themselves and also with the matrix. We have used a novel X-ray diffraction technique on the bulk samples of Inconel 625 at different heattreated conditions to determine the lattice parameters, the lattice misfit of the coherent precipitates with the matrix and their microstructural parameters like size and strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…On one hand, Inconel 625 forms coherent precipitates after heat treatment [15]. Sarkar et al [31] reported that these precipitates show diffracted peaks overlapping to the matrix. Especially the c 00 phase leads to a peak shape also found in the present study.…”
Section: In Situ Segregation Stagementioning
confidence: 99%
“…On one hand, Inconel 625 forms coherent precipitates after heat treatment [15]. Sarkar et al [31] reported that these precipitates show diffracted peaks overlapping to the matrix. Especially the c 00 phase leads to a peak shape also found in the present study.…”
Section: In Situ Segregation Stagementioning
confidence: 99%
“…Wang et al [11] compared the interplanar spacings (dhkl) of 316 stainless steel with those of the Ni-based superalloy 182, and obtained a mismatch of 16% which together with the residual strains ( Figure 14) increased the number of dislocations in the PGS zone and, consequently, its hardness. Based on these considerations, it is believed that the PGS zone of 9%Ni steel cladded with Ni-based superalloy 625 displays similar behavior because of the deformation of this zone during the welding (Figure 14) and the difference in dhkl between these materials, which was about 21% [60]. During the welding of the 2nd L C II, the PGS zone was reheated, which could aid its recovery, thereby softening it.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Thermal aging occurs when a metal is held at a consistent temperature for a long duration, and the increased temperature enables the rearrangement of atoms within the lattice. Within nickel-based alloys precipitates often form as a result of thermal aging [184,164].…”
Section: Evolution Of Microstructure Under Irradiationmentioning
confidence: 99%
“…Thermally aged defects, such as long range ordered precipitates that occur in nickel-based alloys [164,89], also act as barriers to glide dislocation motion. Often these defects are modeled with either the the dispersed barrier hardening model introduced for FCC irradiation defects or as antiphase boundary sheared particles [89].…”
Section: Strengthening Due To Irradiation and Thermal Agingmentioning
confidence: 99%
See 1 more Smart Citation